When Did Coloring Books Become Mindful? Exploring the Effectiveness of a Novel Method of Mindfulness-Guided Instructions for Coloring Books to Increase Mindfulness and Decrease Anxiety - Mantzios, Michail; Giannou, Kyriaki (Frontiers in Psychology, 2018)
Mindfulness has been associated with the use of coloring books for adults; however, the question of whether they do increase mindfulness has not been addressed. In two studies, we attempted to identify whether mindfulness is increased, and whether there is a need for ongoing guidance while coloring, similar to mindfulness meditation. In the first randomized controlled experiment, university students (n = 88) were assigned to an unguided mandala coloring group (i.e., described in mainstream literature as a mindfulness practice) or to a free-drawing group. Measurements of state mindfulness and state anxiety were taken pre- and post- experiment. Results indicated no change in mindfulness or anxiety. In the second randomized controlled experiment, university students (n = 72) were assigned to an unguided mandala coloring group (i.e., same as Experiment 1), or, to a mindfulness-guided coloring group (i.e., same as the unguided coloring group with a mindfulness practitioner guiding participants as in mindfulness breathing meditation, with instructions modified and applied to coloring). Results indicated that the mindfulness-guided mandala coloring group performed better in decreasing anxiety, but no change was observed in mindfulness. Exit interviews revealed that some participants did not like the voice guiding them while coloring, which suggested further differing and significant findings. While mindfulness-guided coloring appears promising, guidance or instructions on how to color mindfully may require further development and adjustment to enhance health and wellbeing.